Pengaruh Substitusi Tepung Sukun pada Pembuatan Kue Nastar terhadap Kualitas Fisik dan Daya Terima Konsumen - Firmansyach, Fajar; Singamurni, I. G. A. N.; Ridawati, Ridawati (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to evaluate the effect of breadfruit (Artocarpus communis) flour substitution in making Nastar cakes on physical quality and consumer acceptability. Breadfruit is known as an alternative food source that is rich in carbohydrates, vitamins and minerals. With a high water content, fresh breadfruit is easily damaged and requires further processing, one of which is to make flour. This research was conducted at the Pastry and Bakery Laboratory, Jakarta State University, using breadfruit flour with substitution percentages of 10%, 20% and 30%. The research method involves organoleptic tests and physical tests on the nastar cakes produced. Samples were tested by 25 untrained panelists using a hedonic scale for aspects of color, aroma, texture, stickiness and taste. Organoleptic data were analyzed descriptively qualitatively, while physical data were analyzed using the Completely Randomized Design (RAL) ANOVA Test and the Friedman Test for consumer acceptability. The results showed that the substitution of breadfruit flour affected several aspects of the physical and organoleptic quality of nastar cake. Nastar cake with 20% substitution of breadfruit flour is most preferred in terms of color, therefore nastar cake with 10% substitution is most preferred in terms of stickiness. There were no significant difference in the aroma and crumb texture aspects. In terms of sweetness, nastar cake substituted with 20% and 30% breadfruit flour showed the same good results as 10% nastar cake. The conclusion of this research shows that breadfruit flour has the potential as a partial substitute for wheat flour in making pineapple cakes without reducing physical quality and consumer acceptability. This can be an alternative for diversifying locally based food products and reducing dependence on imported wheat flour.